An IoT-enabled heart disease prediction framework using hybrid and multi-dilated convolution aided adaptive residual attention network - A. Moorthy; V. Sarala; C. Sivasankar; S. Parthiban; U. Samson Ebenezar (Physical and Engineering Sciences in Medicine, 2026)

Relative effectiveness of high-dose versus standard-dose influenza vaccine against hospitalizations and mortality according to Charlson Comorbidity Index: A post-hoc analysis of the DANFLU-1 randomized trial - Katrine Feldballe Bernholm; Niklas Dyrby Johansen; Caroline Espersen; Daniel Modin; Kira Janstrup Hyldekær; Joshua Nealon; Sandrine Samson; Matthew M. Loiacono; Rebecca C. Harris; Carsten Schade Larsen; Anne Marie Reimer Jensen; Nino Emanuel Landler; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose The DANFLU-1 trial suggested lower incidence of hospitalizations for pneumonia and influenza, respiratory disease and all-cause mortality among older adults receiving high-dose (HD-IV) versus standard-dose (SD-IV) influenza vaccine. This study assessed the relative effectiveness of HD-IV versus SD-IV according to comorbidity in elderly individuals. Methods This was a post-hoc analysis of the DANFLU-1 randomized controlled feasibility trial of HD-IV versus SD-IV conducted during the 2021–2022 influenza season in adults aged 65–79 years. Outcomes assessed included influenza-related, respiratory, and cardiovascular hospitalizations, and mortality. We tested for effect modification by level of the Charlson Comorbidity Index (CCI) using ICD-10 codes up to 10 years prior to randomization. Results Of the 12,477 randomly assigned participants (mean age 71.7 ± 3.9 years, 47.1% female), 8,020 (64.3%) had CCI = 0, 3,560 (28.5%) had CCI = 1–2 and 893 (7.2%) had CCI ≥ 3. When comparing HD-IV with SD-IV, hazard ratios of hospitalizations for pneumonia and influenza were similar across CCI groups (HR [95%CI]: 0.15 [0.03–0.68] for CCI = 0, 0.36 [0.11–1.15] for CCI = 1–2, 1.00 [0.25-4.00] for CCI ≥ 3). Comparable patterns were found for hospitalizations for respiratory disease (0.46 [0.17–1.20] for CCI = 0, 0.67 [0.32–1.39] for CCI = 1–2, 0.66 [0.24–1.87] for CCI ≥ 3) and all-cause mortality (0.28 [0.09–0.86] for CCI = 0, 0.70 [0.30–1.63] for CCI = 1–2, 0.57 [0.24–1.36] for CCI ≥ 3). There was no statistical evidence of effect modification by CCI for any outcome. Conclusions The lower incidences of clinical outcomes for HD-IV compared to SD-IV were not significantly modified by CCI. The potential benefit of HD-IV versus SD-IV may therefore be applicable regardless of comorbidity burden. Further research is required to confirm these findings.

P05-02 Impact of sub-chronic dioxin exposure on the cardiorenal syndrome - R. Courcoux; R. Souktani; G. Berge; M. Quétin; M. Le Garff; S. Placier; C. Samson; J. Hadchouel; M. Gervais (Toxicology Letters, 2025)

Interactive effects of crop types and nitrogen sources on N2O emissions in a cool humid climate - Joannie D’Amours; David E. Pelster; Martin H. Chantigny; Andrew C. VanderZaag; Erin L. Smith; Gilles Bélanger; Émilie Maillard; Marie-Élise Samson; Edward G. Gregorich; Denis A. Angers; Isabelle Royer; Marie-Noëlle Thivierge (Plant and Soil, 2025)
Aims Perennial forages in rotation with annual crops can improve agricultural resilience by increasing soil organic carbon. However, how nitrogen (N) sources interact with rotation diversity to influence soil nitrous oxide (N 2 O) emissions is not well understood. Methods During three snow-free seasons, N 2 O emissions, crop yields, and ancillary variables were measured at three experimental sites with contrasting soil textures (silty clay and sandy loam) in eastern Canada. Using a split-plot design, we compared a corn ( Zea mays L.)-soybean ( Glycine max [L.] Merr.)-corn rotation and a mixed perennial grass sward receiving N via: i) mineral fertilizer (MIN), ii) liquid dairy manure (LDM), and iii) inclusion of alfalfa ( Medicago sativa L.) to the perennial forages with no additional N (LEG). Results When summed across sites over all three years, cumulative N 2 O emissions were greater for LDM than MIN in annual crops (8.75 ± 1.63 and 5.15 ± 0.96 kg N 2 O-N ha –1 , respectively), but not in perennial grasses (2.95 ± 0.55 and 3.76 ± 0.70 kg N 2 O-N ha –1 , respectively). When comparing N sources within each crop type over the three years, MIN generated greater yields than LDM in annual and perennial crops, but lower yield-scaled N 2 O emissions than LDM in annual crops only. During forages post-seeding years, area- and yield-scaled N 2 O emissions induced by LDM and LEG were lower than MIN. Conclusion Our results suggest that for a cool humid climate using LDM or LEG in perennial forages and MIN on annual crops can reduce overall N 2 O emissions, while generating similar or lower yield-scaled emissions.

Structured decision-making shows broad support from diverse stakeholders for habitat conservation and restoration in Kenya’s Central Highlands - Gwili E.M. Gibbon; Martin Dallimer; Hassan Golo; Humphrey Munene; Charlene A. Wandera; Monda N. Edson; Jane C. Gachura; Tim Hobbs; Festus Ihwagi; Stephen R. Ikhamati; Samson K. Ikiara; David Kimathi; et al. (Land Use Policy, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Impact of Urbanization on Temperature Trend Using Geospatial Techniques in Ondo State, Nigeria - Michael C. Ochei; Samson O. Ogunfuyi (Remote Sensing in Earth Systems Sciences, 2023)

Influence of pH and salts on DMF-DMA derivatization for future Space Applications - D. Boulesteix; A. Buch; J. Samson; M. Millan; J. Jomaa; D. Coscia; V. Moulay; O. McIntosh; C. Freissinet; J.C. Stern; C. Szopa (Analytica Chimica Acta, 2023)

Validating a semi-quantitative food frequency questionnaire to assess regional diet in a study of cancer in South West Nigeria - Marguerite L. Samson; Noah C. Peeri; Olusegun Isaac Alatise; Kelli O’Connell; Avinash Sharma; Samson Gbenga Ogunleye; Adewale A. Aderounmu; Olalekan Olasehinde; Akinjide Olurotimi Ogundokun; Abiodun Victor Ikujenlola; Adesegun Fatusi; T. Peter Kingham; et al. (Cancer Causes & Control, 2023)

Juxtaposing Caenorhabditis elegans-Pathogenic Mould Model with Other Models; How Reliable Is This Nematode Model? A Mini Review - Chukwuemeka Samson Ahamefule; Blessing C. Ahamefule; Anthony C. Ike; James C. Ogbonna; Anene N. Moneke (Current Microbiology, 2023)

Pesticide analytical screening system (PASS): A novel electrochemical system for multiplex screening of glyphosate and chlorpyrifos in high-fat and low-fat food matrices - Durgasha C. Poudyal; Vikram Narayanan Dhamu; Manish Samson; Sriram Muthukumar; Shalini Prasad (Food Chemistry, 2023)

Coral reef carbonate accretion rates track stable gradients in seawater carbonate chemistry across the U.S. Pacific Islands - Hannah C. Barkley; Thomas A. Oliver; Ariel A. Halperin; Noah V. Pomeroy; Joy N. Smith; Rebecca M. Weible; Charles W. Young; Courtney S. Couch; Russell E. Brainard; Jennifer C. Samson (Frontiers in Marine Science, 2022)
The U.S. Pacific Islands span a dramatic natural gradient in climate and oceanographic conditions, and benthic community states vary significantly across the region’s coral reefs. Here we leverage a decade of integrated ecosystem monitoring data from American Samoa, the Mariana Archipelago, the main and Northwestern Hawaiian Islands, and the U.S. Pacific Remote Island Areas to evaluate coral reef community structure and reef processes across a strong natural gradient in pH and aragonite saturation state (Ω ar ). We assess spatial patterns and temporal trends in carbonate chemistry measured in situ at 37 islands and atolls between 2010 and 2019, and evaluate the relationship between long-term mean Ω ar and benthic community cover and composition (benthic cover, coral genera, coral morphology) and reef process (net calcium carbonate accretion rates). We find that net carbonate accretion rates demonstrate significant sensitivity to declining Ω ar , while most benthic ecological metrics show fewer direct responses to lower-Ω ar conditions. These results indicate that metrics of coral reef net carbonate accretion provide a critical tool for monitoring the long-term impacts of ocean acidification that may not be visible by assessing benthic cover and composition alone. The perspectives gained from our long-term, in situ , and co-located coral reef environmental and ecological data sets provide unique insights into effective monitoring practices to identify potential for reef resilience to future ocean acidification and inform effective ecosystem-based management strategies under 21st century global change.

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Behavioral Response Study on Seismic Airgun and Vessel Exposures in Narwhals - Mads Peter Heide-Jørgensen; Susanna B. Blackwell; Outi M. Tervo; Adeline L. Samson; Eva Garde; Rikke G. Hansen; Manh Cu’ò’ng Ngô; Alexander S. Conrad; Per Trinhammer; Hans C. Schmidt; Mikkel-Holger S. Sinding; Terrie M. Williams; et al. (Frontiers in Marine Science, 2021)
One of the last pristine marine soundscapes, the Arctic, is exposed to increasing anthropogenic activities due to climate-induced decrease in sea ice coverage. In this study, we combined movement and behavioral data from animal-borne tags in a controlled sound exposure study to describe the reactions of narwhals, Monodon monoceros , to airgun pulses and ship noise. Sixteen narwhals were live captured and instrumented with satellite tags and Acousonde acoustic-behavioral recorders, and 11 of them were exposed to airgun pulses and vessel sounds. The sound exposure levels (SELs) of pulses from a small airgun (3.4 L) used in 2017 and a larger one (17.0 L) used in 2018 were measured using drifting recorders. The experiment was divided into trials with airgun and ship-noise exposure, intertrials with only ship-noise, and pre- and postexposure periods. Both trials and intertrials lasted ∼4 h on average per individual. Depending on the location of the whales, the number of separate exposures ranged between one and eight trials or intertrials. Received pulse SELs dropped below 130 dB re 1 μPa 2 s by 2.5 km for the small airgun and 4–9 km for the larger airgun, and background noise levels were reached at distances of ∼3 and 8–10.5 km, respectively, for the small and big airguns. Avoidance reactions of the whales could be detected at distances >5 km in 2017 and >11 km in 2018 when in line of sight of the seismic vessel. Meanwhile, a ∼30% increase in horizontal travel speed could be detected up to 2 h before the seismic vessel was in line of sight. Applying line of sight as the criterion for exposure thus excludes some potential pre-response effects, and our estimates of effects must therefore be considered conservative. The whales reacted by changing their swimming speed and direction at distances between 5 and 24 km depending on topographical surroundings where the exposure occurred. The propensity of the whales to move towards the shore increased with increasing exposure (i.e., shorter distance to vessels) and was highest with the large airgun used in 2018, where the whales moved towards the shore at distances of 10–15 km. No long-term effects of the response study could be detected.

Occurrence of pathogens in Pacific lamprey (Entosphenus tridentatus) - Aaron D. Jackson; Mary L. Moser; Sam T. Onjukka; Scott LaPatra; Kenneth M. Lujan; Corie Samson; Melissa G. White; Marilyn Blair; Linda Rhodes; Ralph Lampman; Alexa N. Maine; Jeffrey C. Jolley (Reviews in Fish Biology and Fisheries, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Isotherm and Kinetic Evaluation of Dialium guineense Seed Husk and Its Modified Derivative as Efficient Sorbent for Crude Oil Polluted Water Treatment - Samson I. Eze; Kovo G. Akpomie; Chidinma C. Ezeofor; Abduljeleel A. Osunkunle; Obianuju B. Maduekwe; Obinna U. Okenyeka (Water Conservation Science and Engineering, 2019)

Hydrochemical characteristics and quality assessment of groundwater from fractured Albian carbonaceous shale aquifers around Enyigba-Ameri, southeastern Nigeria - Olufemi V. Omonona; Joseph O. Amah; Samson B. Olorunju; Salome H. Waziri; Amobi C. Ekwe; Degree N. Umar; Sylvester W. Olofinlade (Environmental Monitoring and Assessment, 2019)

The complete mitochondrial genome of a stream loach (Schistura reticulofasciata) and its phylogeny - C. Siva; Rohit Kumar; Lata Sharma; M. A. Laskar; Samson Sumer; Ashoktaru Barat; Prabhati Kumari Sahoo (Conservation Genetics Resources, 2018)

New Penicillium and Talaromyces species from honey, pollen and nests of stingless bees - Renan N. Barbosa; Jadson D. P. Bezerra; Cristina M. Souza-Motta; Jens C. Frisvad; Robert A. Samson; Neiva T. Oliveira; Jos Houbraken (Antonie van Leeuwenhoek, 2018)

Four novel Talaromyces species isolated from leaf litter from Colombian Amazon rain forests - Neriman Yilmaz; Carlos A. López-Quintero; Aída Marcela Vasco-Palacios; Jens C. Frisvad; Bart Theelen; Teun Boekhout; Robert A. Samson; Jos Houbraken (Mycological Progress, 2016)

Aureobasidium melanogenum: a native of dark biofinishes on oil treated wood - Elke J. van Nieuwenhuijzen; Jos A. M. P. Houbraken; Martin Meijer; Olaf C. G. Adan; Robert A. Samson (Antonie van Leeuwenhoek, 2016)

I-C-SEA Change: A participatory tool for rapid assessment of vulnerability of tropical coastal communities to climate change impacts - Wilfredo Y. Licuanan; Maricar S. Samson; Samuel S. Mamauag; Laura T. David; Roselle Borja-del Rosario; Miledel Christine C. Quibilan; Fernando P. Siringan; Ma. Yvainne Y. Sta. Maria; Norievill B. España; Cesar L. Villanoy; Rollan C. Geronimo; Olivia C. Cabrera; et al. (Ambio, 2015)

Solid-state synthesis of isostructural tetrachlorometallate salts of amodiaquine: crystal structure of [CdCl4][C20H24ClN3O] - Adedibu C. Tella; Samson O. Owalude; Nzikahyel Simon; Rotimi O. Arise (Medicinal Chemistry Research, 2015)

Ocean feedback to tropical cyclones: climatology and processes - Swen Jullien; Patrick Marchesiello; Christophe E. Menkes; Jérôme Lefèvre; Nicolas C. Jourdain; Guillaume Samson; Matthieu Lengaigne (Climate Dynamics, 2014)

Reflex testing for Lynch syndrome: If we build it, will they come? Lessons learned from the uptake of clinical genetics services by individuals with newly diagnosed colorectal cancer (CRC) - E. Tomiak; A. Samson; N. Spector; M. Mackey; C. Gilpin; E. Smith; D. Jonker; J. Allanson; T. Asmis (Familial Cancer, 2014)

Penicillium subrubescens, a new species efficiently producing inulinase - S. Mansouri; J. Houbraken; R. A. Samson; J. C. Frisvad; M. Christensen; D. E. Tuthill; S. Koutaniemi; A. Hatakka; P. Lankinen (Antonie van Leeuwenhoek, 2013)

Legume seeders of the Cape Floristic Region inhabit more fertile soils than congeneric resprouters—sometimes - Simon C. Power; Michael D. Cramer; G. Anthony Verboom; Samson B. M. Chimphango (Plant Ecology, 2011)

Different spatial memory systems are involved in small- and large-scale environments: evidence from patients with temporal lobe epilepsy - L. Piccardi; A. Berthoz; M. Baulac; M. Denos; S. Dupont; S. Samson; C. Guariglia (Experimental Brain Research, 2010)

Does phosphate acquisition constrain legume persistence in the fynbos of the Cape Floristic Region? - Simon C. Power; Michael D. Cramer; G. Anthony Verboom; Samson B. M. Chimphango (Plant and Soil, 2010)

Leptotrichia hongkongensis sp. nov., a novel Leptotrichia species with the oral cavity as its natural reservoir - Patrick C. Y. Woo; Samson S. Y. Wong; Jade L. L. Teng; Kit-Wah Leung; Antonio H. Y. Ngan; Dong-qing Zhao; Herman Tse; Susanna K. P. Lau; Kwok-Yung Yuen (Journal of Zhejiang University-SCIENCE B, 2010)

Applying the HAZUS-MH software tool to assess seismic risk in downtown Ottawa, Canada - S. K. Ploeger; G. M. Atkinson; C. Samson (Natural Hazards, 2010)

New taxa of Neosartorya and Aspergillus in Aspergillus section Fumigati - Seung-Beom Hong; Hyeon-Dong Shin; Joonbae Hong; Jens C. Frisvad; Per V. Nielsen; János Varga; Robert A. Samson (Antonie van Leeuwenhoek, 2008)

Effects of the toxic dinoflagellate, Alexandrium fundyense on three species of larval fish: a food‐chain approach - J. C. Samson; S. E. Shumway; J. S. Weis (Journal of Fish Biology, 2008)
Sublethal behavioural effects of exposure to paralytic shellfish toxins (PST; saxitoxin and its derivatives) from the toxic dinoflagellate Alexandrium fundyense were investigated in newly settled winter flounder Pseudopleuronectes americanus , larval sheepshead minnow Cyprinodon variegatus and larval mummichog Fundulus heteroclitus through an A. fundyense –copepod–fish food chain. Consumption of as few as six to 12 toxin‐containing copepods was lethal to the fishes. After consuming fewer toxin‐containing copepods, all three fish species exhibited sublethal effects from vector‐mediated exposure. Prey‐capture ability of mummichogs was reduced in larvae that had consumed toxic copepods, Coullana canadensis . After consuming toxic C. canadensis or mixed copepods, mummichog larvae had reduced swimming performance. Swimming activity was also significantly reduced in winter flounder after consuming toxic copepods, including time spent in motion and distance travelled. Prey capture and predator avoidance were reduced in first‐feeding sheepshead minnow larvae that had consumed toxic dinoflagellate cells. Adverse effects on prey capture or predator avoidance may reduce larval survival and facilitate the transmission of PST through the food web. This study provides baseline information on sublethal effects of PST exposure on fishes using a novel food‐chain approach with zooplankton as vectors.

Can the HGM classification of small, non-peat forming wetlands distinguish wetlands from surface water geochemistry? - Nicholas A. Azzolina; Donald I. Siegel; James C. Brower; Scott D. Samson; Martin H. Otz; Ines Otz (Wetlands, 2007)

Decreased expression of Intestinal I- and L-FABP levels in rare human genetic lipid malabsorption syndromes - S. Guilmeau; I. Niot; J. P. Laigneau; H. Devaud; V. Petit; N. Brousse; R. Bouvier; L. Ferkdadji; C. Besmond; L. P. Aggerbeck; A. Bado; M. E. Samson-Bouma (Histochemistry and Cell Biology, 2007)

Evaluation of lethal and non‐lethal sampling methods for the detection of white sturgeon iridovirus infection in white sturgeon, Acipenser transmontanus (Richardson) - J D Drennan; S E LaPatra; C A Samson; S Ireland; K F Eversman; K D Cain (Journal of Fish Diseases, 2007)
Pectoral fin tissue of white sturgeon was investigated as a potential non‐lethal sample source for the detection of white sturgeon iridovirus (WSIV) infection. Histopathology and polymerase chain reaction (PCR) results using fin tissue were compared with the standard lethal histopathology sampling method that utilizes head tissue. Tissues for each of the three sampling methods were collected weekly for 8 weeks from individual sturgeon undergoing an experimental cohabitation challenge with fish infected with the Abernathy isolate of WSIV. Non‐lethal fin histopathological evaluation did not reveal infection during the first 3 weeks of sampling, while non‐lethal PCR and the lethal method were variable. However, all three sampling methods were equally capable of identifying infection from 4 to 8 weeks post‐exposure. Of the survivors tested, all were negative by PCR and the lethal method, and only one fish was identified as being positive by non‐lethal fin histopathology. In another experiment, all three sampling methods were applied to asymptomatic WSIV carriers in a case study conducted at the Kootenai Tribal Sturgeon Conservation Hatchery. Results showed that both lethal and non‐lethal fin histopathology were equally effective in detecting infection, but PCR was unable to identify this strain of WSIV. Depending on the virus isolate, these results suggest that non‐lethal sampling of fin tissue (histopathology or PCR) is comparable with the lethal sampling method at identifying WSIV infection once infection is established, and under certain circumstances may provide an alternative to lethal sampling.

Effect of danofloxacin (Advocin A180) on goats affected with contagious caprine pleuropneumonia - U. Ozdemir; G. R. Loria; K. S. Godinho; R. Samson; T. G. Rowan; C. Churchward; R. D. Ayling; R. A. J. Nicholas (Tropical Animal Health and Production, 2006)

Effect of primary culture medium composition on high frequency somatic embryogenesis in different Coffea species - N. P. Samson; C. Campa; L. Le Gal; M. Noirot; G. Thomas; T. S. Lokeswari; A. de Kochko (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Aspergillus vadensis, a new species of the group of black Aspergilli - Ronald P. de Vries; Jens C. Frisvad; Peter J. I. van de Vondervoort; Kim Burgers; Angelina F. A. Kuijpers; Robert A. Samson; Jaap Visser (Antonie van Leeuwenhoek, 2005)

Penicillium persicinum, a new griseofulvin, chrysogine and roquefortine C producing species from Qinghai province, China - Long Wang; Han-Bai Zhou; Jens C. Frisvad; Robert A. Samson (Antonie van Leeuwenhoek, 2004)

Exploring the Penicillium marneffei genome - Kwok-yung Yuen; Géraldine Pascal; Samson S. Y. Wong; Philippe Glaser; Patrick C. Y. Woo; Frank Kunst; James J. Cai; Elim Y. L. Cheung; Claudine Médigue; Antoine Danchin (Archives of Microbiology, 2003)

High-resolution genetic mapping of the pepper (Capsicum annuum L.) resistance loci Me3 and Me4 conferring heat-stable resistance to root-knot nematodes (Meloidogyne spp.) - C. Djian-Caporalino; L. Pijarowski; A. Fazari; M. Samson; L. Gaveau; C. O’Byrne; V. Lefebvre; C. Caranta; A. Palloix; P. Abad (Theoretical and Applied Genetics, 2001)

Crop rotation and residue management effects on carbon sequestration, nitrogen cycling and productivity of irrigated rice systems - C. Witt; K.G. Cassman; D.C. Olk; U. Biker; S.P. Liboon; M.I. Samson; J.C.G. Ottow (Plant and Soil, 2000)

Nucleotide sequence of the 5′-terminus of Newcastle disease virus and assembly of the complete genomic sequence: agreement with the “rule of six” - R. J. Phillips; A. C. R. Samson; P. T. Emmerson (Archives of Virology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Penicillium discolor, a new species from cheese, nuts and vegetables - Jens C. Frisvad; Robert a. Samson; Birgitte R. Rassing; Marjolein I. van der Horst; F.T.J. van Rijn; J. Stark (Antonie van Leeuwenhoek, 1997)

The Newcastle disease virus V protein binds zinc - M. Steward; A. C. R. Samson; W. Errington; P. T. Emmerson (Archives of Virology, 1995)

Detection of potato leafroll virus by visual inspection, direct tissue blotting and ELISA techniques - J. L. Whitworth; R. G. Samson; T. C. Allen; A. R. Mosley (American Journal of Potato Research, 1993)

Evaluation of direct tissue blotting to detect potato viruses - Richard G. Samson; Thomas C. Allen; Jonathan L. Whitworth (American Journal of Potato Research, 1993)

Sequence analysis of temperature sensitive and ?neuraminidase-tolerant? mutants of Newcastle disease virus (strain Beaudette C) - J. Hughes; K. Yusoff; R. Hardy; H. McCartney; P. T. Emmerson; A. C. R. Samson (Archives of Virology, 1991)

Chemotaxonomy of the genus Talaromyces - J. C. Frisvad; O. Filtenborg; R. A. Samson; A. C. Stolk (Antonie van Leeuwenhoek, 1990)

On the taxonomy of the entomogenous fungus Filobasidiella arachnophila - R. A. Samson; J. A. Stalpers; A. C. M. Weijman (Antonie van Leeuwenhoek, 1983)

A taxonomic study of the Penicillium chrysogenum series - R. A. Samson; R. Hadlok; Amelia C. Stolk (Antonie van Leeuwenhoek, 1977)